The maternal embryonic leucine zipper kinase (MELK) is upregulated in high-grade prostate cancer - Kuner, Ruprecht; Fälth Savitski, Maria; Pressinotti, Nicole Chui; Brase, Jan Christoph; Puig, Sabrina Balaguer; Metzger, Jennifer; Gade, Stephan; Schäfer, Georg; Bartsch, Georg; Steiner, Eberhard; Klocker, Helmut; Sültmann, Holger (Journal of molecular medicine, 2013)
Loss of cell cycle control is a prerequisite for cancer onset and progression. In prostate cancer, increased activity of cell cycle genes has been associated with prognostic parameters such as biochemical relapse and survival. The identification of novel oncogenic and druggable targets in patient subgroups with poor prognosis may help to develop targeted therapy approaches. We analyzed prostate cancer and corresponding benign tissues (n = 98) using microarrays. The comparison of high- and low-grade tumors (Gleason score ≥ 4 + 3 vs. ≤ 3 + 4) revealed 144 differentially expressed genes (p < 0.05). Out of these, 15 genes were involved in the cell cycle process. The gene maternal embryonic leucine zipper kinase (MELK) was identified to be highly correlated with cell cycle genes like UBE2C, TOP2A, CCNB2, and AURKB. Increased MELK gene expression in high-risk prostate cancer was validated by qPCR in an independent patient cohort (p < 0.005, n = 79). Immunohistochemistry analysis using a tissue microarray (n = 94) revealed increased MELK protein expression in prostate cancer tissues of high Gleason scores. RNAi-based inhibition of MELK in PC3 and LNCaP cells suggested putative function in chromatin modification, embryonic development and cell migration. The concerted inhibition of MELK and other cell cycle targets by the antibiotic siomycin A strongly impaired cell viability of prostate cancer cells, and may point to a novel therapy approach for a subset of high-risk prostate cancer patients.